2016
DOI: 10.1111/sjpe.12112
|View full text |Cite
|
Sign up to set email alerts
|

Industry‐specific exchange rate volatility and intermediate goods trade in Asia

Abstract: This paper empirically analyzes the effect of exchange rate volatility on intra-Asian trade of intermediate goods at an industry level by constructing a new dataset of the industry-specific bilateral real exchange rate. As the final processed exports are destined for countries outside the Asian region, both the exchange rate and world demand are considered as a possible driving force in the cross-border fragmentation and processing trade. It is found that, in contrast to the recent studies, the exchange rate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The LnVOL variable, which is a proxy of exchange rate volatility, has a negative relationship to LnRGDP, but it is not significant. This result is reasonable since it is in line with some of the previous findings which reveal that exchange rate volatility only has a negative and significant impact on the general machinery industry and parts of the electric machinery industry [16]. In addition, exchange rate volatility has a negative, but very small, effect on exports [17].…”
Section: A Empirical Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The LnVOL variable, which is a proxy of exchange rate volatility, has a negative relationship to LnRGDP, but it is not significant. This result is reasonable since it is in line with some of the previous findings which reveal that exchange rate volatility only has a negative and significant impact on the general machinery industry and parts of the electric machinery industry [16]. In addition, exchange rate volatility has a negative, but very small, effect on exports [17].…”
Section: A Empirical Resultssupporting
confidence: 89%
“…Specifically, four kinds of short-term and long-term exchange rate volatility in intra-Asian trade on intermediate goods at the industry level results showed that exchange rate volatility has a negative and significant impact only on the general machinery industry and parts of the electric machinery industry with more differentiated products [16]. The different effects of exchange rate volatility in those industries are closely related to the characteristics of the goods traded in each industry.…”
Section: B Previous Findingsmentioning
confidence: 96%
See 1 more Smart Citation
“…Nonetheless, while the positive impact of volatility presented on trade of machinery and transport equipment between Japan and USA, it showed mixed results on chemicals products and miscellaneous manufactured articles (Bahmani-Oskooee and Hegerty, 2008). Sato et al (2016) added that the impact of volatility depends on the characteristics of the trading goods. For instance, the volatility negatively affected trade in general machinery, whereas it had no impact of trade of intermediate goods for the intra-Asia trade.…”
Section: Studies In General Casesmentioning
confidence: 99%
“…In last one decade, the region substantially improved their regional trade, investment and intra-regional production network; however, establishment of regional currency management policy in East Asia remains under doubt. Moreover, Sato et al (2016) claim that negative effect of exchange rate volatility in Asian trade is industry-specific (only for some machinery industry) and cannot be generalized. Thus, importance of regional currency management in East Asia becomes questionable over time.…”
Section: Introductionmentioning
confidence: 99%